Design optimization of inner and outer‐rotor PMSGs for X‐ROTOR wind turbines - Reza Yazdanpanah; Seyed Abolfazl Mortazavizadeh; Mohammad Salehian; David Campos‐Gaona; Olimpo Anaya‐Lara (IET Renewable Power Generation)
Abstract This article presents an analytical design approach for the inner and outer rotor Permanent Magnet Synchronous Generators (PMSGs) that are a key component of wind turbines. By developing the analytical model, sensitivity analysis has been performed to determine the effect of some important geometrical and electromagnetic parameters on the generator's output characteristics. The GA optimization algorithm was used to find optimized designs in terms of efficiency, weight, cost, and temperature rise. In order to find the global optimization solution within the allowed variable range and in accordance with the constraints, a combined objective function has also been defined. In order to validate the analytical model, ANSYS electromagnetic and thermal simulations have been used. With this approach, the designer is provided with a good understanding of the input parameters and constraints in light of the application requirements.